“Education in Law” and Laws in Education - L. S. Grebnev (Высшее образование в России)
Using examples of the introduction of the Unified State Exam and participation in the Bologna process, the article analyzes changes in the regulatory framework for budgetary financing of education as a reaction to external circumstances. The role of the family and educational institutions in fostering a sense of responsibility for decisions and the results of their implementation is also discussed.